Analisis Efektivitas Sosialisasi Pemilu oleh Diskominfo Kuningan dalam Meningkatkan Partisipasi Pemilih di Desa - Hendri Suwarsono; Fathan Rizki H; Dedeh Ermawati; Fachrizal Habbib AN; Ilham Arya Wiguna (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
Low voter participation in rural areas is often a problem in elections. Effective socialization is considered as one way to increase voter awareness and participation. This study aims to analyze the effectiveness of election socialization conducted by the Kuningan Regency Communication and Information Office in increasing voter participation in rural areas. This study uses a qualitative approach with data collection techniques through interviews and observations. The research participants consisted of villagers, election officers, and related parties involved in the socialization. The results showed that the socialization of elections conducted by the Kuningan Regency Communication and Information Office was effective in increasing public awareness and knowledge about elections. This has an impact on increasing voter participation in rural areas. However, there are challenges in reaching certain groups of people, especially those who live in remote areas and have limited access to information. While socialization has been successful in increasing participation, there is still a need for a more inclusive and adaptive approach to local conditions. This research recommends utilizing social media and other interactive methods, such as hands-on training or the use of technology, to more effectively reach hard-to-reach groups.